2010
DOI: 10.1007/s12031-010-9432-z
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Enhances LPS-Induced IL-1β Expression in Microglia via the Extracellular Signal-Regulated Kinase 1/2 Pathway

Abstract: The extracellular signal-regulated kinase (ERK) is involved in the cytokine production of immune cells. In this study, we show the influence of xenon on phosphatase activity, ERK 1/2 signalling and cytokine expression in microglia. The murine microglia cell line BV-2 was treated with 50 ng/ml lipopolysaccharide (LPS) and 74% xenon in 21% O(2) and 5% CO(2). Cytokine levels were examined by gene expression analysis, Western blot and enzyme-linked immunosorbent assay. Phosphatase inhibition was assessed with p-ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…In vitro investigations suggest that xenon has pro-inflammatory effects, increasing TNF-α and IL-6 [66], and IL-1β [67] in LPSmediated cultures. A recent study on adults did not show any differences in leucocyte function in peripheral blood with xenon compared to sevoflurane [63].…”
Section: Inhalational Anestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro investigations suggest that xenon has pro-inflammatory effects, increasing TNF-α and IL-6 [66], and IL-1β [67] in LPSmediated cultures. A recent study on adults did not show any differences in leucocyte function in peripheral blood with xenon compared to sevoflurane [63].…”
Section: Inhalational Anestheticsmentioning
confidence: 99%
“…Xenon is an odorless noble gas, normally present in traces in Earth's atmosphere, and it has been used as volatile anesthetic [64]. It has shown hemodynamic stability, fast recovery and neuroprotective proprieties but high costs [65].In vitro investigations suggest that xenon has pro-inflammatory effects, increasing TNF-α and IL-6 [66], and IL-1β [67] in LPSmediated cultures. A recent study on adults did not show any differences in leucocyte function in peripheral blood with xenon compared to sevoflurane [63].…”
mentioning
confidence: 99%
“…Transcripts of an exon-intron spanning hypoxanthine guanine phosphoribosyl transferase (HPRT) served as control for cDNA purity (BioTaq TM PCR Kit, Bioline, Luckenwalde, Germany). Real-time PCR (RT-PCR) analysis was performed with the SensiMix SYBR Green Kit (Quantace, Bioline Hamburg, Germany) on a MyIQ qRT-PCR detection system (Bio-Rad) as described previously [20]. Transcripts of interleukin (IL)-1b (s CTGTGTCTTTCCCGTGGACC; as CAGCTCAT ATGGGTCCGACA), as well as CCL2 (s TTAAAAACC TGGATCGGAACCAA; as GCATTAGCTTCAGATTTA CGGGT), CXCL10 (s TAGCTCAGGCTCGTCAGTTCT; as GATGGTGGTTAAGTTCGTGCT), CXCL11 (s GGC TTCCTTATGTTCAAACAGGG; as GCCGTTACTCGGG TAAATTACA) and LIF (s GCCTCCCTGACCAATA TCACCCG; as GACGGCAAAGCACATTGCTG) were amplified.…”
Section: Real-time Pcr (Rt-pcr)mentioning
confidence: 99%
“…Transcripts of interleukin (IL)-1b (s CTGTGTCTTTCCCGTGGACC; as CAGCTCAT ATGGGTCCGACA), as well as CCL2 (s TTAAAAACC TGGATCGGAACCAA; as GCATTAGCTTCAGATTTA CGGGT), CXCL10 (s TAGCTCAGGCTCGTCAGTTCT; as GATGGTGGTTAAGTTCGTGCT), CXCL11 (s GGC TTCCTTATGTTCAAACAGGG; as GCCGTTACTCGGG TAAATTACA) and LIF (s GCCTCCCTGACCAATA TCACCCG; as GACGGCAAAGCACATTGCTG) were amplified. Relative amounts of transcripts were calculated with the delta CT-method and normalized to transcripts (s TGACCACAGTCCATGCCATC; as GACGCACACA TTGGGGGTAG) of a reference housekeeping gene (glucose aldehyde phosphate dehydrogenase, GAPDH) [20]. Its stable expression compared to other housekeeping genes was tested beforehand (data not shown).…”
Section: Real-time Pcr (Rt-pcr)mentioning
confidence: 99%
“…[9] It can enhance lipopolysaccharide-induced interleukin-1 beta (IL-1β) expression in microglia by activating extracellular signal-regulated kinase 1/2, [10] inhibiting caspase-3 activation and cytochrome c release from cells, [11] and reducing serum levels of the pro-inflammatory cytokines, such as IL-1, IL-6, and tumor necrosis factor alpha (TNFα) in rats. [12,13] In addition, in recent years, it was shown that xenon had neuroprotective, cardioprotective, and renoprotective effects in different animal models subjected to preconditioning, real-time conditioning, and postconditioning.…”
Section: Introductionmentioning
confidence: 99%